2022
DOI: 10.1002/ajhb.23805
|View full text |Cite
|
Sign up to set email alerts
|

Water insecurity, self‐reported physical health, and objective measures of biological health in the Peruvian Amazon

Abstract: Objectives: This study examines the associations between water insecurity, self-reported physical health, and objective measures of biological health among 225 Awajún adults (107 women; 118 men) living in the Peruvian Amazon, a "water-abundant" region. Methods: A survey, which included multiple measures of self-reported physical health, and objective measures of biological health such as blood pressure and nutritional and immune biomarkers. Results: Greater water insecurity was associated with multiple measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Blood pressure (BP) is frequently used as an indicator of stress but is influenced by hydration and environmental factors. This physiological process helps explain why there has been mixed evidence to date on the association between WI and BP (Brewis et al 2019a, Tallman et al 2022). Dehydration and hotter temperatures both lower BP, yet WI may increase risk of dehydration (Rosinger 2018).…”
Section: Figurementioning
confidence: 94%
“…Blood pressure (BP) is frequently used as an indicator of stress but is influenced by hydration and environmental factors. This physiological process helps explain why there has been mixed evidence to date on the association between WI and BP (Brewis et al 2019a, Tallman et al 2022). Dehydration and hotter temperatures both lower BP, yet WI may increase risk of dehydration (Rosinger 2018).…”
Section: Figurementioning
confidence: 94%
“…Tallman, Valdes-Velasquez, et al (2022) compared diets among the Awajún of the Peruvian Amazon in the 1970s and in 2013 and found that community members now only eat a fraction of aquatic species previously recognized as important. These changes in diet were attributed to larger ecological changes due to highway construction and were accompanied by the emergence of higher levels of obesity and anaemia among the Awajún (Tallman, Collins, et al, 2022;Tallman, Riley-Powell, et al, 2022;Tallman, Valdes-Velasquez, et al, 2022), suggesting that diverse aquatic food sources buffer against the development of chronic disease.…”
Section: Microsystem (Individual)mentioning
confidence: 99%
“…The majority of research on this topic has been conducted in water‐scarce areas (Wutich, 2020). However, there is an emerging group of studies documenting water insecurity in ‘water abundant’ areas such as the Amazon rainforest in South America (Rosinger, 2018; Tallman, Collins, et al., 2022; Tallman, Riley‐Powell, et al., 2022; Tallman, Valdes‐Velasquez, et al., 2022; Torres‐Slimming et al., 2020), the Congo and Chad River basins in Africa (Nagabhatla et al., 2021), the Mekong region of Southeast Asia (Sithirith, 2021) and in communities throughout North America (Eichelberger, 2018; Martin et al., 2021). These studies highlight how anthropogenic changes related to climate change and extractive industries produce water insecurity and how water insecurity influences human health, particularly that of Indigenous peoples and local communities (IPLCs) (Leonard et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies have shown that lack of clean water is associated with food insecurity, diarrheal disease, heightened blood pressure, poor mental health, and poor perceived health. [2][3][4][5][6] It is therefore essential to improve water-related intervention efforts.Sabana Larga is a rural community of approximately 230 families located in the province of Dajabon on the Northwest region of the Dominican Republic. The community relies heavily on rivers and streams for domestic water use including bathing, washing, cleaning, and cooking.…”
mentioning
confidence: 99%
“…1 Studies have shown that lack of clean water is associated with food insecurity, diarrheal disease, heightened blood pressure, poor mental health, and poor perceived health. [2][3][4][5][6] It is therefore essential to improve water-related intervention efforts.…”
mentioning
confidence: 99%